A review of the genus Neogreenia MacGillivray (Hemiptera: Coccomorpha: Qinococcidae) with descriptions of two new species - Zheng, Xinyi; Watson, Gillian W.; Zhang, Jiangtao; Tan, Zhixiang; Wu, San’an (Zootaxa, 2024)
The species of Neogreenia MacGillivray (Hemiptera: Coccomorpha: Qinococcidae) are reviewed. The genus is distributed in the Oriental and Palaearctic Regions and now contains seven species. The present study provides updated generic descriptions of all the developmental stages and a brief account of the biology and life cycle of Neogreenia. The genotype, Neogreenia zeylanica (Green, 1896), is redescribed. The following are described and illustrated for the first time: the second-instar nymph, third-instar female, and male third-instar nymph and pupa of N. zizyphi Tang; the second-instar nymph of N. lonicera Wu & Nan; and the second-instar nymph of N. sophorica Wu. Two new species are described and illustrated: Neogreenia ficus Zheng & Wu, sp. n. based on the adult female and Neogreenia tangi Zheng & Wu, sp. n. based on all female instars. These new species bring the total number of described species of Neogreenia to seven. An identification key to all the developmental stages of Neogreenia, and identification keys to species based on adult females and available nymphal instars are provided.